VENTURE CAPITAL INVESTMENT CRITERIA IN GAME SOFTWARE COMPANIES : Initial investments in the Finnish game industry - Valkonen, Ville (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis explores venture capital (VC) investment criteria on a specific industry, the game industry. The game industry is a new, lucrative and fast-paced industry characterised by volatility, unpredictability and a hit-driven nature. The theoretical purpose is to summarise the findings of previous literature on VC investment criteria and discuss it in the context of the game industry. The empirical purpose is to study what criteria Finnish VCs use when deciding whether to invest or not into a game company. To aid in providing an appropriate framework, the thesis includes a section introducing venture capital activities in general and in Finland, and the game industry, its dynamics and the Finnish game industry. The methodological approach of the thesis is empirical and descriptive. The thesis falls into the tradition of ‘managerial-oriented venture capital research’, which approaches VC activities from the micro-perspective in contrast to ‘market-oriented venture capital research’, which has a macro-perspective. The study is qualitative and the data is received via semi-structured interviews. In total six persons are interviewed: five from venture capitalists and one from the Finnish Game Industry Association. The primary result from the interviews is that an experienced team is the most important single investment criterium, accompanied with product and/or business model continuity, market characteristics such as market size, platform or segment, product characteristics such as genre, novelty, appeal, market interest and having a playable demo ready, substantial profit potential and VC portfolio suitability. The team needs to be experienced in both content and technical skills, have game business understanding, have marketing skills, be balanced, have passion and have the ability to execute. Moreover, the importance of the continuity of the product or business model was a new finding that seems to be important to VCs operating in the game industry. Market characteristics seem to play a role in some VC’s decision making, but are not universally critical to all VCs. Similarly, product characteristics divide the interviewees. Portfolio suitability and substantial profit potential did not stand out. In conclusion, the key findings of this thesis can be summarised in that the game industry does not fundamentally differ from general VC investment criteria, but certain criteria are emphasised. General VC investment criteria - the competitiveness of entrepreneur and the team, the lucrativeness of the market, the suitability of the product or service and profitable financial considerations - are all relevant, but the team is clearly even more emphasised when investing into the game industry. Future research is suggested in VC investment criteria in different industries and game industry related financial topics.